SWC-TPS Workshop of Synchrotron-Based X-ray Spectroscopies on Energy Materials. Issue 2 (4th March 2017) - Zhong, Jun; Huang, Di-Jing; Sun, Xuhui; Sham, Tsun-Kong
Abstract : The SWC-TPS Workshop of Synchrotron-Based X-ray Spectroscopies on Energy Materials took place November 15–17, 2016, on the Dushu Lake Campus of Soochow University, Suzhou, Jiangsu, China. The workshop was co-organized by the Soochow University–Western University Centre for Synchrotron Radiation Research (SWC or the Centre) and Institute of Functional Nano & Soft Materials (FUNSOM), Soochow University.